PERAN KONSELOR SEKOLAH UNTUK PENANGANAN KEKERASAN SEKSUAL PADA ANAK - Kartika Nur Fathiyah (Paradigma, 2010)
Children sexual abuse becomes a national issue. All forms of children sexual abuse are highly affect children physically, mentally and view of themselves, other around of the children and also their performance in schools. Usually, schools are the first place to see the evidence of sexual abuse and school counselors are primarily responsible for giving treatment to abused children sexually. Consequently, school counselors must be aware of that symptoms, so, they can monitor the well-being of children. In addition, school counselors must learn the intervention strategies for helping students who suffered from sexual abuse to survive and overcome their experiences. This article will explain anything about children sexual abuse and school counselors’ strategies to help sexually abused children.Keywords: child sexual abuse, school counsellor, interventionstrategies